2016
DOI: 10.3389/fpls.2016.00978
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biomass, Mineral Composition, and Quality of Cardoon in Response to NO3-:Cl- Ratio and Nitrate Deprivation from the Nutrient Solution

Abstract: Leaf extracts of cultivated cardoon (Cynara cardunculus L. var. altilis DC) are an important source of phenols. Soilless culture represents an important and alternative tool to traditional agriculture, since it allows a precise control of plant nutrition and the maximization of yield and quality of the product. Reducing N supply, while keeping quantity as high as possible is desirable for environmental and health-related reasons, especially that N deficiency can lead to improved concentrations of secondary pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 67 publications
3
43
0
Order By: Relevance
“…An appropriate nutrient formula and management would minimize this harm without losses in yield or nutritional value (Bar-Yosef et al, 2009). Short-term fertilization break has been considered to be a reliable method for reducing the NO 3 hazard (Borgognone et al, 2016). Our results showed that the yield of all tested plants increased, and NO 3 contents declined, after the fertilization break treatment, which is consistent with the reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An appropriate nutrient formula and management would minimize this harm without losses in yield or nutritional value (Bar-Yosef et al, 2009). Short-term fertilization break has been considered to be a reliable method for reducing the NO 3 hazard (Borgognone et al, 2016). Our results showed that the yield of all tested plants increased, and NO 3 contents declined, after the fertilization break treatment, which is consistent with the reports.…”
Section: Discussionsupporting
confidence: 92%
“…Excessive applications of NO 3 in fertilizers during the late stages of vegetative growth have more impact on NO 3 accumulation in leafy vegetables than when applied during early stages because requirements for N decrease as plants mature (Blom-Zandstra and Lampe, 1983). For this reason, fertilization management during preharvest is an effective way to reduce NO 3 accumulation and increase nutritional value without loss in yield (Borgognone et al, 2016;Malagoli et al, 2004).…”
mentioning
confidence: 99%
“…The linear reduction in nitrate content with increasing NaCl concentration in the irrigation water is associated to the antagonism effect between nitrate and chloride. Rubinigg et al (2003) and Borgognone et al (2016) showed that in the presence of high chloride levels, root-to-shoot translocation of nitrate could be reduced at the site of entrance into xylem parenchyma cells through competition for the same channel. High level of NaCl in irrigation water or the growing medium hampers plant physiological processes such as photosynthesis as well as water relations (Munns, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this kind of system water is being efficiently recirculated in order to achieve maximum and precise nutrient assimilation by plants. Using hydroponics, it is possible to modulate bioactive compounds score by controlling the nutrient solution composition (Borgognone, Rouphael, Cardarelli, Lucini, & Colla, ; Lucini et al, ).…”
Section: Introductionmentioning
confidence: 99%